Achalasia: A Review of Etiology, Pathophysiology, and Treatment - Nor Hedayanti; Supriono Supriono (The Indonesian Society for Digestive Endoscopy, 2016)
Achalasia was a condition marked by peristaltic movement absent in lower esophageal sphincter and segment that hypertonic result in imperfect relaxation during food ingestion. Achalasia incidence did not differ between men and women, account for 1 in 100.000 people every year with prevalence of 10 in 100.000 people, unrelated specifically with ethnic, and has its highest incidence on 30-60 age group.Based on its etiology, it was divided into primary and secondary Achalasia, while based on its motility, it was into hypermotil, hypomotil, and amotil Achalasia. Until present, several therapeutic modalities were available to treat Achalasia, among them was pharmacology therapy, botulinum toxin injection via endoscopy, pneumatic dilatation, Heller myotomy surgery, and Per Oral Endoscopy Myotomy (POEM).